Combining of silk fibroin and Aloe vera gel to fabricate wound dressings - Doan, Vu Nguyen; Tran, Ha Le Bao (Vietnam Journal of Biotechnology, 2022)
Currently silk fibroin is used more and more in the biomedical researches, including a potential research direction in creating wound dressing. Aloe vera gel has been used as a traditional herbal with many properties suitable for treatment of burns such as anti-inflammatory, anti-bacterial, anti-fungal, especially improvable wound healing. Therefore, the prepared fibroin/ Aloe vera gel film (FAV) was an ideal material for wound dressings. In this study, sericin is removed from the silk to obtain fibroin fiber. Aloe vera gel is purchased from Traditional Medicine Institute, Ho Chi Minh city, Viet Nam. Fibroin fiber and Aloe vera gel are dissolved by formic acid adding calcium chloride (CaCl2). Created FAV are then evaluated in some characteristics such as surface structure, tensile strength, absorbency, dehydration rate, biodegradation ability, preventing bacteria ability and cytotoxicity test. The results showed that FAV possessed good mechanical properties, suitable water vapor transmission rate, effective prevention of bacterial penetration and non-cytotoxic. This study is the first step to creating foundation and orientation for the development of commercial wound dressings.